Suicide Attempt as the Presenting Symptom in a Patient with COVID-19: A Case Report from the United States - Nelson Telles-Garcia; Tyler Zahrli; Gaurav Aggarwal; Sakshi Bansal; Leonard Richards; Saurabh Aggarwal (Case Reports in Psychiatry)
Coronavirus disease 2019 (COVID-19) has attained a pandemic status and is associated with a high morbidity and mortality. Social isolation, fear of ostracization, and illness itself and limited access to care can lead to worsening of mental illnesses. We report a case from the United States describing a young male with a suicidal attempt who was subsequently found to have COVID-19 infection. Further research is needed to evaluate potential factors for this unique association.